Factors Influencing Individual Performance In An Indonesian Government Office - Munawaroh, Azizatul; Riantoputra, Corina D. S.; Marpaung, Sally Bethesda (UI Scholars Hub, 2013)
Reformation in Indonesian government offices leads to many substantial changes, and demands improved job performances while arguably loading employees with more work. This research aims to understand factors that potentially influence job performance in Indonesian government offices that carries on such reformation. Using adapted scales from previous studies, this research investigates the role of workload, responsibility for others (level of responsibility to care for other people) and need for achievement on employee’s performance. A survey to all full-time workers in an Indonesian government office is conducted. Contrary to expectation, workload does not influence employee’s performance. Instead, regression analysis demonstrates that, employee’s need for achievement and responsibility for others are significant factors affecting individual performance. These results are important because they highlight the significance of need for achievement for the success of reformation in this office, and by extension for reformation in Indonesia. The results are also interesting because this is the first study that points out to the role of responsibility for others in influencing individual performance in Indonesia which is characterized by collectivistic culture. This paper discusses the contributions of these results for theory and practice.